Neuronal endolysosomal alterations induced by Apolipoprotein E4 emerge over time in primary neurons - Nyberg, Emma; Konings, Sabine C ; 0000-0003-4008-2779; Lindblom, Nils; Israelsson, Bodil; Klementieva, Oxana ; 0000-0003-1782-050X; Martinsson, Isak; Gouras, Gunnar K ; 0000-0002-5500-6325 (The Journal of biological chemistry, 2025)
Apolipoprotein E4 (ApoE4), the major genetic risk factor for Alzheimer's disease (AD), is vital for understanding cellular processes involved in AD pathogenesis. Evidence implicates endosomes as a central player in AD, where endosomal enlargement in neurons is among the earliest changes in AD. This enlargement was reported to be enhanced in APOE4 carriers. Cells internalize ApoE into endosomes for lipid delivery, and previous studies indicate that ApoE4 influences endosomes. However, the effect of ApoE4 on endosome function seems different depending on cell type, and our understanding of how ApoE4 influences endosomes in mature neurons, the cell type degenerating in AD, remains limited. We aimed to increase understanding of the impact ApoE4 has on endosomal dynamics in primary neurons and whether external triggers, such as time-in-culture/aging, synaptic activity, and cholesterol, influence these endosomal changes. We show that without external triggers, mature primary neurons from ApoE knockout (KO), ApoE3, and ApoE4 mice show no major differences in endosomal appearance and function and adapt similarly to increased synaptic activity. However, with prolonged time in culture, neurons with ApoE4 show reduced degradative ability, along with a decreased number of active lysosomal compartments. Moreover, when supplying aged cultures with cholesterol, ApoE4 neurons have a predisposition to accumulate cholesterol in the endolysosomal system. Taken together, we show that ApoE4 impacts endolysosome function in primary neurons, but that changes emerge only after prolonged time in culture. A better understanding of how ApoE4 impacts neurons could provide important insights into ApoE4-directed therapy for AD.
Copyright © 2025 The Authors. Published by Elsevier Inc. All rights reserved.
Keywords: Animals; Apolipoprotein E4/metabolism; Neurons/metabolism; Lysosomes/metabolism; Endosomes/metabolism; Mice; Cells, Cultured; Cholesterol/metabolism; Alzheimer Disease/metabolism; Mice, Knockout